Rethinking the Panata to the Nazareno of Quiapo - Espiritu, Wilson Angelo G (Archīum Ateneo, 2023)
Filipino Catholicism’s hallmark is its festive and colorful celebrations of popular piety; which exhibit the Catholic faith’s embeddedness in people’s lives and culture. One of the most renowned Filipino devotions is rendered to Nuestro Padre Jesus Nazareno of Quiapo; Manila. The devotion of making a pledge to the Nazareno; known as panata; is commonly understood as a sacred promise that must be kept in return for a request that is granted. In this paper; I propose a theological reading of panata performance that unites devotion to the Nazareno and commitment to the wellbeing of others. This interpretation aims to orient panata as a form of lived Filipino Catholicism that converges popular spirituality and socio-political responsibility. I flesh out this constructive proposal using three steps. I begin by tracing the historical roots of the Nazareno devotion. Then; I consider narratives of Nazareno devotees about the confluence of their devotion and their socio-political engagement. Finally; based on these narratives; I theologically reframe the panata to the Nazareno as a catalyst for mystical-political praxis. Through this fresh outlook; the panata’s theological significance is reconsidered beyond popular piety towards becoming a vehicle for Christ’s saving work amid the Philippine society.